CFD Investigation of General Electric Gas Turbine Wash Nozzle - Amiruddin, Ahmad Yusuf (IRC, 2018)
Compressor cleaning is used to solve the issue of fouling that happens at the compressor blades of the gas turbine. Fouling phenomenon does affect the overall performance of the gas turbine by causing the power output and thermal efficiency to drop as a result the significant decreased rate of airflow and compressor isentropic efficiency. Fouling simply deteriorates the aerodynamic design effectivity of compressor blades by dissipations of dust or any other foreign particles on the blades. This project has the objective to conduct optimization to gas turbines that belongs to Malaysia Liquified Natural Gas (MLNG), Bintulu in terms of compressor cleaning. CFD investigation by Discrete Phase Modelling (DPM) that are available in ANSYS Fluent are used to simulate the compressor cleaning system to check for its effectiveness. Mund and Pilidis (2006) stated in their study that effectiveness of the cleaning mechanism can be measured and determined by looking at the spray area by the wash nozzles at the inlet guide vane (IGV) of the gas turbine. The developed approach was used to simulate the compressor washing system of GE MS6001 gas turbine model. Simulation parameters that will be looked into includes the number of nozzles used, nozzle position, nozzle type, nozzle diameter, injection velocity, velocity of air intake. As well as the droplet size, fluid density and injection velocity and injection flowrate. The main parameters that were tested are injection velocity and nozzle half cone angle, to obtain the spray particle concentration on the IGV. Series of simulation were done to obtain the most optimal combination of injection velocity and nozzle half-cone angle, by measuring the highest value of injected particles concentration on the IGV.